Fc-dependent and -independent Platelet Clearance Caused by Anti-CD36 IgG1 and IgG2 Subclasses - Ren, Hui; Chen, Dawei; Luo, Yalin; Xu, Xiuzhang; Xia, Wenjie; Ye, Xin; He, Jiansen; Xu, Yaori; Liu, Jing; Luo, Shengxue; Liang, Huaqin; Santoso, Sentot; Fu, Yongshui (Thrombosis and Haemostasis, 2026)
Anti-CD36 isoantibodies can induce platelet transfusion refractoriness and fetal neonatal immune thrombocytopenia. However, the mechanism of platelet clearance mediated by these antibodies (Abs) in such disorders remains unknown.We analyzed platelet clearance caused by mouse and human CD36 monoclonal Abs GZ1 IgG1 and IgG2 subclasses in vitro and in vivo.Platelet clearance was evaluated in vitro by platelet phagocytosis assays and in vivo by monoclonal Ab GZ1 administration to C57BL/6J mice. Platelet activation, apoptosis, and desialylation were analyzed by flow cytometry.Both anti-CD36 Abs subclasses caused lower platelet clearance than anti-αIIbβ3 owing to the FcγR occupancy of monocytes by anti-CD36 Abs. This reaction could lead to mild thrombocytopenia, compared with the severe thrombocytopenia induced by anti-αIIbβ3 platelet-specific Abs. IgG subclass-mediated platelet clearance was inhibited by anti-FcγR Abs and intravenous immunoglobulin (IVIG). The human IgG2 Ab subclass caused lower platelet clearance than IgG1. IgG1- and IgG2-mediated platelet phagocytosis was inhibited by anti-FcγRI and anti-FcγRII, respectively. Unlike IgG1, the IgG2 Ab subclass induced platelet activation, apoptosis, and desialylation and platelet clearance by endothelial cells via Fc-independent pathway.IgG1 and IgG2 subclasses of anti-CD36 Abs triggered platelet clearance primarily via the Fc-dependent pathway. The IgG2 Ab subclass, however, additionally induced platelet clearance via the Fc-independent pathway. These results indicate that the anti-CD36 Ab IgG subclass influences platelet clearance efficiency and may therefore determine the severity of immune thrombocytopenia caused by anti-CD36 antibodies.
Keywords: CD36; platelet clearance; Fcγ receptor